FORM AND FLOW OF THE ACADEMY OF SCIENCES ICE CAP, SEVERNAYA ZEMLYA, RUSSIAN HIGH ARCTIC - Dowdeswell J.A.; Gorman M.R.; Bassford R.P.; Williams M.; Glazovsky A.F.; Macheret Y.Y.; Shepherd A.P.; Vasilenko Y.V.; Savatyuguin L.M.; Hubberten H.-W.; Miller H. (My University, 2002)
The 5,575-km2 Academy of Sciences Ice Cap is the largest in the Russian Arctic. A 100-MHz airborne radar, digital Landsat imagery, and satellite synthetic aperture radar (SAR) interferometry are used to investigate its form and flow, including the proportion of mass lost through iceberg calving. The ice cap was covered by a 10-km-spaced grid of radar flight paths, and the central portion was covered by a grid at 5-km intervals: a total of 1,657 km of radar data. Digital elevation models (DEMs) of ice surface elevation, ice thickness, and bed elevation data sets were produced (cell size 500 m). The DEMs were used in the selection of a deep ice core drill site. Total ice cap volume is 2,184 km3 (~5.5 mm sea level equivalent). The ice cap has a single dome reaching 749 m. Maximum ice thickness is 819 m. About 200 km, or 42%, of the ice margin is marine. About 50% of the ice cap bed is below sea level. The central divide of the ice cap and several major drainage basins, in the south and east of the ice cap and of up to 975 km2, are delimited from satellite imagery. There is no evidence of past surge activity on the ice cap. SAR interferometric fringes and phase-unwrapped velocities for the whole ice cap indicate slow flow in the interior and much of the margin, punctuated by four fast flowing features with lateral shear zones and maximum velocity of 140 m yr-1. These ice streams extend back into the slower moving ice to within 5-10 km of the ice cap crest. They have lengths of 17-37 km and widths of 4-8 km. Mass flux from these ice streams is ~0.54 km3 yr-1. Tabular icebergs up to ~1.7 km long are produced. Total iceberg flux from the ice cap is ~0.65 km3 yr-1 and probably represents ~40% of the overall mass loss, with the remainder coming from surface melting. Driving stresses are generally lowest (<40 kPa) close to the ice cap divides and in several of the ice streams. Ice stream motion is likely to include a significant basal component and may involve deformable marine sediments.